Human temporal lobe epilepsy analyses by tissue proteomics. Issue 6 (28th February 2014) - Mériaux, Céline; Franck, Julien; Park, Dan Bi; Quanico, Jusal; Kim, Young Hye; Chung, Chun Kee; Park, Young Mok; Steinbusch, Harry; Salzet, Michel; Fournier, Isabelle
ABSTRACT Although there are many types of epilepsy, temporal lobe epilepsy (TLE) is probably in humans the most common and most often studied. TLE represents 40% of the total epilepsy form of the disease and is difficult to treat. Despite a wealth of descriptive data obtained from the disease history of patients, the EEG recording, imaging techniques, and histological studies, the epileptogenic process remains poorly understood. However, it is unlikely that a single factor or a single mechanism can cause many changes associated with this neuropathological phenomenon. MALDI mass spectrometry imaging (MSI) coupled to protein identification, because of its ability to study a wide range of molecules, appears to be suitable for the preparation of molecular profiles in TLE. Seven neuropeptides have been have been identified in Dental gyrus regions of the hippocampus in relation with TLE pathology. Shot‐gun studies taking into account gender influence have been performed. Tissue microextraction from control (10) toward 10 TLE patients have been analyzed after trypsin digestion followed by separation on nanoLC coupled to LTQ orbitrap. From the shot‐gun analyses, results confirmed the presence of specific neuropeptides precursors and receptors in TLE patients as well as proteins involved in axons regeneration including neurotrophins, ECM proteins, cell surface proteins, membrane proteins, G‐proteins, cytoskeleton proteins and tumor suppressors. Among the tumor suppressors identified, the Leucine‐rich glioma inactivated 1 (LGI1) protein was found. LGI1 gene recently been demonstrated being implicated in heritability of TLE. We have also demonstrate the presence a complete profile of tumor suppressors in TLE patients, 7 have been identified. Refining this analysis taken into account the gender influence in both control and in TLE reflected the presence of specific proteins between male and female and thus mechanisms in pathology development could be completely different. © 2014 Wiley Periodicals, Inc.